Mensches in the trenches : Jewish foot soldiers in the anti-apartheid struggle - Ancer, Jonathan (Batya Bricker, 2021)
"The defeat of Apartheid and triumph of non-racial democracy in South Africa was not the work of just a few individuals. Ultimately, it came about through the actions - large and small - of many principled, courageous people from all walks of life and backgrounds. Some of these activists achieved enduring fame and recognition and their names today loom large in the annals of the anti-apartheid struggle. Others were engaged in a range of practical, hands-on activities outside of the public eye. These were the loyal foot soldiers of the liberation Struggle, the unsung workers at the coal face who, largely behind the scenes, made a difference on the ground and helped to bring about meaningful change. Even though Apartheid was aimed at entrenching white power and privilege, a number of whites rejected that system and instead joined their fellow South Africans in opposing it. Of these, a noteworthy proportion came from the Jewish community. Mensches in the Trenches tells the hitherto unrecorded stories of some of these activists and the essential, if seldom publicised role that they and others like them played in bringing freedom and justice to their country." --